2020
DOI: 10.1186/s12889-020-08674-w
|View full text |Cite
|
Sign up to set email alerts
|

The association between sialolithiasis and smoking, alcohol drinking and obesity in Korea: a nested case-control study

Abstract: Background: Smoking and alcohol consumption are the most common social habits in patients with sialolithiasis. Moreover, obesity has been reported to have a significant association with poor oral hygiene, one of the causes of sialolithiasis. The purpose of this study was to evaluate the relationships among tobacco smoking, drinking alcohol, obesity and sialolithiasis in a Korean population. Methods: The Korean National Health Insurance Service-Health Screening Cohort, which includes patients ≥40 years old, was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…However, based on our experience and the literature review, endoscopic sialolith removal does not result in sialolith formation. Regarding the habit, a previous study found a positive association between sialolithiasis and tobacco smoking in a population of ≤ 40 years-old 36 . And considering the systemic metabolism, sialoliths tend to be unilateral, which argues against a systemic metabolism and suggests local factors play major roles 37 .…”
Section: Discussionmentioning
confidence: 92%
“…However, based on our experience and the literature review, endoscopic sialolith removal does not result in sialolith formation. Regarding the habit, a previous study found a positive association between sialolithiasis and tobacco smoking in a population of ≤ 40 years-old 36 . And considering the systemic metabolism, sialoliths tend to be unilateral, which argues against a systemic metabolism and suggests local factors play major roles 37 .…”
Section: Discussionmentioning
confidence: 92%
“…The symptoms and effects of dry mouth depend on these flow rates [ 27 ]. It has also been shown that smoking has an adverse effect on the quantity and quality of an individual’s saliva [ 18 , 28 , 29 ]. Therefore, the evidence supports that female smokers have a higher risk of developing dry mouth, as shown by the results of the present study with regard to female daily smokers and female non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Os fatores etiológicos desta patologia ainda não são claros, hipóteses incluem questões anatômicas, que afetam a formação ou o fluxo salivar, e fatores composicionais, como aumento do teor de cálcio e funções enzimáticas alteradas, infecção, inflamação, trauma físico do ducto ou da glândula (Hammett & Walker, 2019). Alguns hábitos também podem ser relacionados a sialolitíase como a diminuição da ingestão de líquidos, medicamentos que reduzem o fluxo salivar e o tabaco (Jin et al, 2020;Ungari et al, 2022).…”
Section: Introductionunclassified